Ocular biometry and pathology in captive and free-ranging southern white rhinoceros (Ceratotherium simum simum) and south-central black rhinoceros (Diceros bicornus minor) in South Africa - Goodhead, Antony Denzil (University of Pretoria, 2024)
Mini Dissertation (MMedVet (Ophthalmology))--University of Pretoria, 2024.